The predictive value of common symptoms in early pregnancy for complications later in pregnancy and at birth. (27th October 2022) - Ertmann, Ruth Kirk; Nicolaisdottir, Dagny Ros; Kragstrup, Jakob; Overbeck, Gritt; Kriegbaum, Margit; Siersma, Volkert
Abstract: Introduction: The aim was to investigate whether common pregnancy‐related symptoms—nausea, vomiting, back pain, pelvic girdle pain, pelvic cavity pain, vaginal bleeding, itching of vulva, pregnancy itching, leg cramps, uterine contractions and varicose veins—in the first trimester of pregnancy add to the identification of women at high risk of future pregnancy and birth complications. Material and methods: Survey data linked to national register data. All women booking an appointment for a first prenatal visit in one of 192 randomly selected General Practices in East Denmark in the period April 2015–August 2016. The General Practices included 1491 women to this prospective study. Two outcomes, pregnancy complications and birth complications, were collected from the Danish Medical Birth Register. Results: Among the 1413 included women, 199 (14%) experienced complications in later pregnancy. The most serious complication, miscarriage, was experienced by 65 women (4.6%). Other common pregnancy complications were gestational diabetes mellitus ( n = 11, 0.8%), gestational hypertension without proteinuria ( n = 34, 2.4%), mild to moderate preeclampsia ( n = 34, 2.4%) and gestational itching with effect on liver ( n = 17, 1.2%). Women who experienced pelvic girdle pain, pelvic cavity pain or vaginal bleeding in the first trimester of pregnancy had a higher risk of pregnancy complications later on in later pregnancy. None of the other examined symptoms showed associations to pregnancy complications. No associations were found between pregnancy‐related physical symptoms in first trimester and birth complications. Conclusions: Symptoms in early pregnancy do not add much information about the risk of pregnancy or birth complications, although pain and bleeding may give reason for some concern. This is an important message to women experiencing these common symptoms and to their caregivers. Abstract : Women who experienced pelvic girdle pain, pelvic cavity pain or vaginal bleeding in the first trimester of pregnancy had a higher risk of later pregnancy complications, but we found no significant associations between any early pregnancy symptoms and birth complications.